2021
DOI: 10.1177/17562864211054962
|View full text |Cite
|
Sign up to set email alerts
|

FAST-ED scale smartphone app-based prediction of large vessel occlusion in suspected stroke by emergency medical service

Abstract: Background and Purpose: Considering the highly time-dependent therapeutic effect of endovascular treatment in patients with large vessel occlusion–associated acute ischemic stroke, prehospital identification of large vessel occlusion and subsequent triage for direct transport to a comprehensive stroke center offers an intriguing option for optimizing patient pathways. Methods: This prospective in-field validation study included 200 patients with suspected acute ischemic stroke who were admitted by emergency me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…According to the results, though EMS utilization was not associated with the proportion of patients receiving endovascular therapy within 90 min, the adjusted time for imaging-to-puncture and door-to-puncture was significantly shorter in the EMS group. Recent research has developed and validated various tools to identify large vessel occlusion strokes in the prehospital setting enabling rapid triage and timely treatment of patients [27][28][29][30][31][32]. Efforts for prehospital risk identification for eligible endovascular patients in the EMS system may further optimize endovascular therapy and improves outcomes [33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, though EMS utilization was not associated with the proportion of patients receiving endovascular therapy within 90 min, the adjusted time for imaging-to-puncture and door-to-puncture was significantly shorter in the EMS group. Recent research has developed and validated various tools to identify large vessel occlusion strokes in the prehospital setting enabling rapid triage and timely treatment of patients [27][28][29][30][31][32]. Efforts for prehospital risk identification for eligible endovascular patients in the EMS system may further optimize endovascular therapy and improves outcomes [33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that its use improved door-to-CT times for 215 intervention patients as compared with 389 controls [27 min (18-44) vs. 71 min (43-147); P ¼ 0.0001] [35]. Similarly, a further study found that an application-based stroke scale used on smartphones in the field achieved good accuracy in detecting LVO [36].…”
Section: Telemedicine Smartphone Applications and Artificial Intellig...mentioning
confidence: 99%